Cadherin‐11 promotes the mechanical strength of engineered elastic cartilage by enhancing extracellular matrix synthesis and microstructure. (6th December 2021) - Li, Jia; Cao, Rui; Wang, Qian; Shi, Hang; Wu, Yi; Sun, Kexin; Liu, Xia; Jiang, Haiyue
Abstract: Limitations of current treatments for auricular cartilage defects have prompted the field of auricular cartilage tissue engineering. To date, inducing the formation of cartilaginous constructs with biochemical and biomechanical properties of native tissue is the final aim. Through hematoxylin‐eosin and immunohistochemistry staining, Cadherin‐11(CDH11) was confirmed highly expressed in the auricular cartilage tissue and chondrocytes. In vitro, by knockdown and overexpression of CDH11 in chondrocytes, CDH11 was demonstrated to promote the expression of collagen type II (COL2A), elastin (ELN), aggrecan (ACAN), and cartilage oligomeric matrix protein (COMP). In addition, the CDH11 overexpressed chondrocytes promoted neo‐cartilage formation and its biomechanical property by increasing the key transcription factor of chondrogenesis SOX9 expression and cartilage extracellular matrix (ECM) production. The young's modulus and yield stress of the neo‐cartilage in CDH11 overexpression group were about 1.7 times ( p = 0.0152) and 2 times ( p = 0.0428) higher than those in control group, respectively. Then, the immunohistochemistry staining, qRT‐PCR and western blot examination results showed that the expression of COL2A and ELN were significantly increased. Notably, the electron microscopy results showed that the collagen and elastic fibers of the neo‐cartilage in CDH11‐OV group arranged in bunches and were more uniform and compact compared to the control group. Furthermore, CDH11 promoted elastic fiber assembly by increasing lysyl oxidase (LOX), fibrillin‐1 (FBN1) expression. Taken together, our results demonstrated that CDH11 improves the mechanical strength of tissue‐engineered elastic cartilage by promoting ECM synthesis and elastic fiber assembly.